Clinical Development of New TB Vaccines: Recent Advances and Next Steps - Hatherill, Mark; White, Richard G.; Hawn, Thomas R. (Frontiers in Microbiology, 2020)
Mycobacterium tuberculosis (Mtb) kills more people worldwide than any single infectious pathogen, yet the only vaccine licensed against tuberculosis, Bacille Calmette Guerin (BCG) is approaching its centenary. Two recent advances in clinical tuberculosis vaccine development have invigorated the field. BCG revaccination of interferon-gamma release assay (IGRA) negative adolescents provided 45% protection against sustained Mtb infection defined by IGRA conversion; and the protein-subunit vaccine M72/AS01E provided 50% protection against progression from Mtb infection to tuberculosis disease in IGRA-positive adults. These findings provide encouraging evidence for pre-exposure and post-exposure approaches to vaccination against tuberculosis, both of which may be necessary to rapidly interrupt the cycle of Mtb transmission and sustain long-term impact on global tuberculosis control. New trials are needed to demonstrate efficacy of M72/AS01E with greater precision, in a wider age range, in diverse epidemic settings, and in populations that include Mtb-uninfected and HIV-infected persons. Modelling the impact of mass campaigns with M72/AS01E and other fast-follower vaccine candidates will be crucial to make the use case and demonstrate public health value for TB endemic countries. The size and scope of the next generation of efficacy trials, and the need to expand and accelerate the existing clinical development pipeline, will require public and private consortium funding and concerted political will.